(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of mechanical warming methods in preventing perioperative hypothermia in patients undergoing lumbar spine surgery. Methods: A prospective cohort study was conducted at Hanoi Medical University Hospital from February 2025 to February 2026 on 80 patients aged ≥ 18 years old, ASA physical status I-III, undergoing lumbar spine surgery under general anesthesia with a duration ≥ 120 minutes. The warming group received active warming with a heating mattress and warmed intravenous fluids, while the non-warming group was covered with standard surgical blankets only. Core body temperature was measured at study time points. Results: Core temperatures at all measured time points were significantly higher in the warming group compared to the non-warming group (p < 0.05). The incidence of hypothermia in the warming group was 17.5%, significantly lower than 57.5% in the non-warming group (p < 0.001). All cases of hypothermia were mild. The proportion of patients without postoperative shivering was higher in the warming group (90%) than in the non-warming group (42.5%). The time to temperature recovery was shorter in the warming group (2.3 ± 8.00 minutes) compared to the non-warming group (24.8 ± 23.4 minutes) (p < 0.001). Conclusion: Mechanical warming is an effective method for preventing perioperative hypothermia in patients undergoing spinal surgery, contributing to improved patient safety and quality of care.